Clinical and microbiological evaluation of ventilator-associated pneumonia in an intensive care unit in Vietnam - Kayoko Hayakawa; Nguyen Gia Binh; Dao Xuan Co; Pham The Thach; Pham Thi Phuong Thuy; Ngo Quy Chau; Mai Lan Huong; Do Van Thanh; Doan Mai Phuong; Tohru Miyoshi-Akiyama; Maki Nagashima; Norio Ohmagari (Elsevier, 2023)
Summary: Background: The increasing incidence of multidrug-resistant Gram-negative bacteria causing ventilator-associated pneumonia (VAP) is a global concern. A better understanding of the epidemiology of VAP in Southeast Asia is essential to optimise treatments and patient outcomes. Methods: VAP epidemiology in an intensive care unit in Vietnam was investigated. A prospective cohort study was conducted. Patients who were ventilated for >48 hours, diagnosed with VAP, and had a positive respiratory culture between October 2015 and March 2017 were included. Whole-genome sequencing (WGS) was performed on Acinetobacter baumannii isolates. Results: We identified 125 patients (137 episodes) with VAP from 1,699 admissions. Twelve patients had 2 VAP episodes. The median age was 60 years (interquartile range: 48-70), and 68.8% of patients were male. Diabetes mellitus was the most frequent comorbidity (N=35, 28%). Acinetobacter baumannii was most frequently isolated in the first VAP episode (N=84, 67.2%) and was multiply resistant to meropenem, levofloxacin, and amikacin. The 30-day mortality rate was 55.2% (N=69) and higher in patients infected with A. baumannii (N=52, 65%). WGS results suggested a complex spread of multiple clones. Conclusions: In an intensive care unit in Vietnam, VAP due to A. baumannii had a high mortality rate, and A. baumannii and K. pneumoniae were multidrug resistant, with carbapenem resistance of 97% and 70%, respectively.